Young of year largemouth bass (Micropterus salmoides) relative abundance and diet: role of habitat type, spatial context, and size. - Mapes, Robert L. (Kansas State University, 2016)
Habitat is a central focus of ecological research and fisheries management. For example, a Web of Science search returned over 88,000 peer-reviewed studies that examined fish habitat, the National Fish Habitat Partnership has invested millions of dollars to “foster fish habitat conservation,” and “essential fish habitat” is a central tenet of marine fisheries policy. The overarching goal of my thesis was to examine the spatial context of fish habitat research in order to improve the effectiveness of fisheries management. To achieve this goal, I quantified approaches to fish habitat used in the peer reviewed literature. Then I tested if approaches to assessing habitat provided different ecological answers to key questions using 1,200 young of year largemouth bass (Micropterus salmoides) collected in Hillsdale Lake, Kansas, in 2014-2015. Within, the fisheries habitat literature, several gaps exist. First, although vegetation was a major focus of young of year largemouth bass habitat research, few studies quantitatively compared young of year largemouth abundance and diet across vegetated and non-vegetated habitats. Second, relatively little of the fisheries habitat literature on young of year largemouth bass explicitly tested habitat type, a common approach used in management and restoration. Third, peer reviewed papers on young of year largemouth bass physical habitat used multiple approaches to studying habitat (local characteristics, habitat type, lakewide characteristics), then often ignored spatial variation completely in interpreting empirical results. Field sampling provided information on several of these gaps. First, young of year largemouth bass were more abundant in vegetation and beach habitats than in rock, wood, or offshore habitats. Young of year largemouth bass utilized beach habitats as often as vegetated habitats. Diets were similar across vegetated and beach habitat types. Second, size of young of year largemouth bass increased through time but size and habitat were not related. My data showed that the size range seen for first year largemouth bass in the first summer in Hillsdale Lake did not alter their distribution or diet. From my research, I make the following recommendations. 1.) Concurrently examine local characteristics, habitat type, and lakewide characteristics with the same data set. 2.) Include insights about different approaches in the discussion of all future fisheries habitat studies. 3.) Continue to test multiple approaches to test fisheries response to habitat. In summary, using different approaches to study young of year largemouth bass habitat use could improve our scientific understanding and aid in restoration and management of reservoir and lake fisheries.
Keywords: HabitatLargemouth Bass